Acupuncture and related therapies for atopic eczema: A protocol for systematic review and network meta-analysis. Issue 50 (16th December 2022) - Li, Wang; Zhang, Kaiqi; Wang, Dongxin; Jiao, Ruimin; Li, Sha; Zhai, Xu
Abstract : Background: Atopic eczema (AE) is a chronic relapsing dermatological disease characterized by pruritus, dryness, erythema, and lichenification. Acupuncture as an alternative treatment can relieve symptoms, reduce the recurrence, and improve the quality of life (QoL) with less adverse reactions in treating AE. This network meta-analysis (NMA) will c omprehensively access the efficacy and safety of different acupuncture therapies for patients with AE, and rank the different acupuncture therapies, in order to present evidence-based medicine evidence for clinical application extensively. Method and analysis: This study will search 8 electronic databases from the establishment of the database to August 30th, 2022. The screening of literature, data extraction, and risk of bias assessment will be conducted by 2 researchers, respectively. The quality of evidence will be judged by the Grading of Recommendations Assessment, Development and Evaluation system. This NMA will be analyzed with Stata Version. 14.0 and WinBUGS Version.1.4.3. Results: This study will comprehensively access the efficacy and safety of different acupuncture therapies for patients with AE on the severity, itch intensity, emotional symptoms, QoL, and recurrence rate. Moreover, it will further identify which acupuncture therapy is the most effective. Conclusion: The findings of this NMA may help patients and therapists choose the best acupuncture therapy in treating AE and furnish reliable evidence for guidelines. Registration number: PROSPERO CRD42020203437